Supplement to the Grasses of Madhya Pradesh - Tiwari, S.D.N. (Indian Forester, 1963)
The author had published description of 201 species of grasses collected from old Madhya Pradesh region in Indian Forester, October and November, 1654 and February and March, 1955. In this supplement, descriptions of additional 38 species and 7 genera is added